He Buys with Heart, She Buys with Thought? A Multi-Group Analysis of Gender Differences in Anthropomorphic Character Effects - Fahrais Zahrudy; Tarysha Aulya Putri Rany (Journal of Studies in Academic, Humanities, Research, and Innovation, 2025)
In a world that is over-designed, anthropomorphic products have moved beyond fad to become symbolic tools that shape the way things are perceived, felt, and acted upon deliberately. The present paper examines the influence of anthropomorphism appeal by three dimensions (appearance anthropomorphism, emotional anthropomorphism, and image anthropomorphism) on consumer purchase decision-making, and product knowledge as a cognitive mediator. Based on the Stimulus-Organism-Response (S-O-R) model, the study used a quantitative research design that surveyed 364 Indonesian consumers of collectibles using purposive sampling. Partial Least Squares Structural Equation Modeling (PLS-SEM) was used to conduct data analyses. The results suggest that visual and thematic attributes of anthropomorphic products positively affect product knowledge which further has a strong positive influence on purchase intention. Emotional anthropomorphism has a direct effect on intention by way of affective involvement as opposed to cognitive elaboration. Multigroup analyses according to gender show that men are more affected by emotional anthropomorphism in the case of visual and thematic clarity, which is contrary to the traditional ideas of female emotional superiority. Taken together, these findings point to two symbolic pathways through which anthropomorphic design works, namely, cognitive and affective. The paper also provides theoretical contributions to the field of symbolic processing in consumer behavior and practical implications to marketers who wish to develop products that not only appeal, but also connect and convert to the consumers.